DEVELOPING ENVIRONMENTAL CULTURE THROUGH LEARNING THE LANDSCAPE GENRE IN FINE ARTS LESSONS - Aslonov Furqat Botirovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the role of the landscape genre in fine arts education as an effective means of developing students’ environmental culture. The study emphasizes how artistic perception of nature, visual thinking, and creative expression can foster ecological awareness and aesthetic appreciation. Through landscape painting, students not only learn the principles of composition, color harmony, and spatial perception, but also develop sensitivity to environmental issues and the beauty of natural surroundings. The article highlights the importance of integrating innovative pedagogical approaches and creative collaboration between teachers and students to nurture environmentally conscious, aesthetically developed personalities.